2003
DOI: 10.1093/annonc/mdg204
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancies following adjuvant chemotherapy:6-year results from a Belgian randomized study comparing cyclophosphamide, methotrexate and 5-fluorouracil (CMF) with an anthracycline-based regimen in adjuvant treatment ofnode-positive breast cancer patients

Abstract: HEC, as delivered in this trial, cannot be recommended in clinical practice because of the lack of superiority over classic CMF and because of the increased risk of AML observed in this arm. Prolongation of conventional anthracycline-based treatment beyond the current standard of four to six cycles is not recommended in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…Over the past few decades, adjuvant chemotherapy for BC has undergone major changes, expanding from the classical cyclophosphamide, methotrexate and 5-fluorouracil (CMF) regimen used in the 1970s, to anthracycline-containing regimens in the 1990s, to the recent incorporation of taxanes (paclitaxel and docetaxel) into anthracycline-based regimens (7)(8)(9)(10) for the treatment of node-positive or even lower-risk patients. In 1976, Bonadonna et al (11) reported the efficacy of CMF as an adjuvant treatment for patients with node-positive BC.…”
Section: Overview Of Adjuvant Therapymentioning
confidence: 99%
“…Over the past few decades, adjuvant chemotherapy for BC has undergone major changes, expanding from the classical cyclophosphamide, methotrexate and 5-fluorouracil (CMF) regimen used in the 1970s, to anthracycline-containing regimens in the 1990s, to the recent incorporation of taxanes (paclitaxel and docetaxel) into anthracycline-based regimens (7)(8)(9)(10) for the treatment of node-positive or even lower-risk patients. In 1976, Bonadonna et al (11) reported the efficacy of CMF as an adjuvant treatment for patients with node-positive BC.…”
Section: Overview Of Adjuvant Therapymentioning
confidence: 99%
“…6 Decisions regarding the use of adjuvant therapy are strongly influenced by the risk of disease recurrence and death. These risks are assessed by examining prognostic factors of breast cancer, such as axillary lymph-node metastasis, age, and some tumor characteristics (e.g., size, histologic and nuclear grades, and estrogen and progesterone receptor status).…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%
“…A separate analysis of this trial by Bernard-Marty noted that a total of 16 patients treated with high-dose EC developed second malignancies, compared with nine for intermediate-dose EC and 11 for CMF. 37 In the highdose EC arm there were three cases of acute myelogenous leukemia (AML) and one case of non-Hodgkin's lymphoma (NHL). Hence, although anthracyclinebased regimens appear more effective overall, they may be associated with an increased risk of second malignancies, especially AML, when anthracyclines are given in high total dose and this needs to be considered when selecting treatment for individual patients.…”
Section: Cmf Versus Other Regimens: Activity Anthracycline-containingmentioning
confidence: 99%
“…The coordinators of this trial concluded that prolongation of conventional anthracycline-based treatment beyond the current standard of four to six cycles is not to be recommended, predominantly because of the increased risk of AML. 37 With respect to second malignancies after taxanebased regimens, most trials are as yet not mature enough to report on second malignancies. However, the CALGB 9344 trial noted no difference in the rate of second malignancies between those patients who received AC only compared with those that received AC followed by paclitaxel.…”
Section: Second Malignanciesmentioning
confidence: 99%